KULIAH KERJA NYATA UNTUK MENDUKUNG PENINGKATAN INDEKS PEMBANGUNAN MANUSIA DI DESA SUKARAME - Julianto, Indri Tri; Citra Indahsari, Ajeng; Arif Syamsudin, Muhammad; Muhammad Ajif, Arvin; Akhdan Hidayat, Fairuz; Arif Rahman, Rifal; Suryani, Isma; Muhammad Sambas, Phadil; Malik Ibrahim, Maulana; Setiawan Putra, Achmad Dhani; Saepul Jamil, Alwis; Huwaidah, Alya; Mutiara, Sani; Agisni Nurlela, Agni; Dwi Anggara, Krisna; Rahman, Jaohari; Ridwan; Abdullah, Angga; Fauzi Pratama, Andhika; Alamsyah, Restu (Jurnal PkM MIFTEK, 2023)
Real Work Lectures (KKN) is a form of implementation of the tridharma of higher education which integrates education, research and community service. The Garut Institute of Technology Thematic KKN in the 2022/2023 Academic Year is a clear example of this concept. In the Bayongbong District area, as many as 403 students from 5 study programs participated in this KKN program, with a focus on Strengthening Village Independence through the Use of Technology to Support Increasing the Human Development Index (HDI) in Sukarame Village. This KKN method is divided into three main stages, namely preparation, implementation and evaluation. During the implementation of KKN, students carry out various programs that cover various important aspects of society. They provide seminars on digital literacy, provide Healthy Home services, assist in tempeh waste management, develop the Kawal Desa Application, improve the quality of Micro, Small and Medium Enterprises (MSMEs) products, and provide education about nutrition and preventing anemia. Apart from these programs, the KKN group also actively participates in activities with the community, such as counseling about waste banks, teaching activities for children, teaching the Koran, environmental cleanup activities every Friday, joint sports activities, as well as various celebration activities in commemoration of Hari Birthday of the Republic of Indonesia. The results of implementing this KKN are clearly visible in improving the quality of life in Sukarame Village, Bayongbong, Garut Regency. A holistic approach that combines education, research and community service has brought significant positive benefits to local communities.